Histomorphologic Analysis of the Late-term Rat Fetus and Placenta. (February 2018) - Charest, Phanie L.; Vrolyk, Vanessa; Herst, Pauline; Lessard, Maryse; Sloboda, Deborah M.; Dalvai, Mathieu; Haruna, Julius; Bailey, Janice L.; Benoit-Biancamano, Marie-Odile
Histological examination of the rat placenta and fetus is uncommon. Toxicological studies mainly rely on gross examination of the fetus and on fetal and placental weights. These are often insufficient to assess the fetal and placental toxicity of xenobiotics. The small size of the fetus makes its dissection labor-intensive. Thus, our objective was to develop a simple and accurate technique to evaluate the rat fetus and placenta. Sprague-Dawley rat fetuses at gestational day 19.5 ( n = 18) and their placentas ( n = 32) were fixed in formalin. Placentas were cut transversally in the center. Fetuses were cut following a freehand whole-body serial sectioning diagram adapted from Wilson's method. Sections were stained with hematoxylin–eosin–phloxine–saffron, and histomorphometry was used to measure the area of the fetal placental region (27.2 ± 1.7 mm 2 ), including the labyrinth (22.2 ± 1.0 mm 2 ) and the basal zone (4.8 ± 0.8 mm 2 ). Our whole-fetus serial sectioning technique resulted in 12 precise cutting planes that fit on 3 histological slides, enabling the examination of most organs without labor-intensive dissection. Quantitative analysis of placental areas improves the understanding of the pathogenesis of treatment-related changes. This technique provides a standardized method for future research in pertinent fields such as developmental biology and toxicology.